Prevalence, Dispersion and Nature of Bioaerosols over a Solid Landfill Site in Central India - Priyanka D. Bhoyar; Pooja Kamdi; Amit Bafana; Panuganti C. S. Devara; Saravanadevi Sivanesan; Amrit Kumar; Kannan Krishnamurthi (Aerosol and Air Quality Research)
Abstract Bioaerosols (or biological aerosols) consist of aerosol particles that originate biologically either as fully active component or as whole or part of inactive fragments. They are ubiquitously present in the atmospheric environment. They are the least investigated pollutants due to their complex structure and composition. The effects of bioaerosols, originating due to the processes, such as wastewater management, handling of sludge, composting, municipal solid waste, and animal facilities, on human health are well recognized. Proper identification, quantification, impacts and exposure threshold levels are essential to understand the nature and impact of bioaerosols on human health and climate. In this communication, we determine the inhalable (PM2.5) particulate matter concentration and embedded bioaerosol (bacteria and fungi) levels over a Municipal Solid Waste (MSW) landfill site in relation to surrounding upwind and downwind locations in Nagpur, India. Measurements were made using an Airmetrics MiniVol air sampler and bioaerosols were analyzed by adopting the culture-based method. A total of 23 fungal and 17 bacterial morphotypes were found in this study. The results showed dominance of bacterial bioaerosol over fungal bioaerosol at the landfill site. The bioaerosol levels were higher at the landfill than the upwind and downwind sites. The bioaerosols did not show any correlation to the PM2.5. In summary, the results indicate abundance of PM2.5, containing both bacterial and fungal bioaerosols, which can pose human health hazards over the study region. In our knowledge, it is the first study of bioaerosols at the landfill site in Nagpur, India.